2015
DOI: 10.1007/s11096-015-0100-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic evaluation and risk factors for drug allergies in children: from clinical history to skin and challenge tests

Abstract: Parent or self-reported drug allergy should be evaluated with a standardized diagnostic work-up before strict prohibitions are made. In addition, family and personal histories of drug allergy were significant risk factors related to allergic drug reactions in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
0
28
1
2
Order By: Relevance
“…Drug desensitization is described as a temporary induction of drug tolerance by the administration of incremental doses of the drug. 47 It is important to realize that drug desensitization is a therapeutic measure for the safe administration * Refs 25,26,28,31,[35][36][37]43,154,155. of a drug to a patient who has either a proven or is highly likely to have a drug allergy as opposed to drug challenge, which is a diagnostic procedure performed in cases of low probability of drug allergy. 23,47 In addition, drug challenge and desensitization should be done in a monitored setting and are contraindicated in patients with severe non-IgE-mediated reactions, such as SJS, TEN, DRESS syndrome, interstitial nephritis, hepatitis, or hemolytic anemia.…”
Section: Drug Desensitizationmentioning
confidence: 99%
“…Drug desensitization is described as a temporary induction of drug tolerance by the administration of incremental doses of the drug. 47 It is important to realize that drug desensitization is a therapeutic measure for the safe administration * Refs 25,26,28,31,[35][36][37]43,154,155. of a drug to a patient who has either a proven or is highly likely to have a drug allergy as opposed to drug challenge, which is a diagnostic procedure performed in cases of low probability of drug allergy. 23,47 In addition, drug challenge and desensitization should be done in a monitored setting and are contraindicated in patients with severe non-IgE-mediated reactions, such as SJS, TEN, DRESS syndrome, interstitial nephritis, hepatitis, or hemolytic anemia.…”
Section: Drug Desensitizationmentioning
confidence: 99%
“…In addition, it has been shown that most of the children with reported hypersensitivity could tolerate macrolides, and macrolide hypersensitivity was confirmed in only 6.2-15.5% of the reported cases [17,18]. In another study in children in our country, the frequency of confirmed macrolide hypersensitivity was 27.2% (3/11) [19]. In this study, the number of patients is lower than in ours, and all confirmed cases had immediate reactions.…”
Section: Discussionmentioning
confidence: 96%
“…Arıkoğlu ve ark. (17) da çocuklardan oluşan çalışma grubunda en sık amoksisilin klavulonik asite karşı reaksiyon bildirmiştir. Aynı çalışmada makrolidler ise en sık non-beta laktam alerji gelişen antibiyotik grubunu oluşturmaktadır).…”
Section: Discussionunclassified
“…Arıkoğlu ve ark. (17), çocuk yaş grubunda ilaç alerjilerinin tanısını %55.1'inde DPT, %44.8'nde İPT yoluyla doğrulamıştır. Çalışmamızda 9'u şüpheli ilaçla olmak üzere 27 DPT uygulandığında şüpheli ilaçlarla yapılanların 4'ünde (%44.4) pozitiflik saptandı.…”
Section: Discussionunclassified